Mental Health Perspective of Religious Psychology - Multi Sari Dewi; Irma Riyani (Gunung Djati Conference Series, 2021)
This study aims to discuss mental health from the perspective of religious psychology. This research method is qualitative through literature study with a religious psychology approach. The results of the discussion of this study include the notion of mental health, mental health criteria, religious psychology, and mental health from the perspective of religious psychology. From this analysis, it can be concluded that the tendency for mental health relations in the psychology of religion originates largely from ancient times. Religion can have a significant impact on human life, including health. Because people who have good health will always feel safe and feel happy under any circumstances, so people in good health will always introspect on all the conditions they do in order to control and control themselves.